In the kingdom of shoes : Bata, Zlín, globalization, 1894-1945 - Doleshal, Zachary Austin (University of Toronto Press, 2021)
"One of the world's largest sellers of footwear, the Bata Company of Zlín, Moravia, has a remarkable history that touches on crucial aspects of what made the world modern. In the twilight of the Habsburg Empire, it Americanized its production model while also trying to Americanize its workforce. In the chaos of postwar Czechoslovakia, it promised a technocratic form of governance. During the Roaring Twenties, Bata became synonymous with rationalization across Europe and thus a flashpoint for a continent-wide debate. In the Great Depression, Bata globalized when others contracted, and in doing so, became the first shoe company to unlock the potential of globalization. As Bata expanded worldwide, it became an example of corporate national indifference, where company personnel were trained to be able to slip into and out of national identifications with ease. Such indifference, however, was seriously challenged by the geopolitical crisis of the 1930s. Bata management turned nationalist, even fascist, on the cusp of the Second World War."--